Reconfiguring the past Visionen für einen Forschungscampus in Dahlem - Pasel, Ralf (CODE / architectural files, 2022)
How can the museum of the future look like? This publication deals with the currently strongly changing landscape of museums in Germany and Berlin. The museum complex in Dahlem is the starting point for the explorations of a place that is to be established as a new type of research location in the next few years. To be able to think of such a research campus at a location that is already anchored in the cultural memory of Berliners and has a positive connotation in society presents itself as a unique opportunity, which the department CODE I Design and Building Construction of the TU Berlin together with the foundation Seize Prussian cultural heritage approaches with numerous illustrated design strategies.